Desenvolvimento de formulações nanotecnológicas para o tratamento da candidíase vulvovaginal - Santos, Sara Saurin dos (2012)
This work aimed the preparation of clotrimazole-loaded nanocapsule suspensions for vulvovaginal fungal infections treatment. For the first time, virgin coconut oil and medium chain triglycerides were used as an oil core of polymeric nanocapsules containing clotrimazole. The analytical method for quantification of this drug into nanoparticles was developed and validated. The method proved to be selective, linear, precise, accurate and robust. Using the method of interfacial deposition of preformed polymer, the nanoparticles were successfully prepared at three different concentrations of clotrimazole (1, 2 and 3 mg/mL). The physicochemical parameters measured were pH, particle diameter, polydispersity index, drug content, encapsulation efficiency, zeta potential and stability in storage during 60 days. The encapsulation efficiency was near to 100%, zeta potential was positive due to the cationic polymer employed, the pH was around 5.6 and drug contents were close to the theoretical values. The size distribution was nanometer (140-200 nm) with polydispersity index lower than 0.2. The formulations had adequate physicochemical characteristics and were stable during storage. Photodegradation studies have shown that the nanoencapsulation improved the stability of clotrimazole against UVC radiation compared to free drug solution after 14 hours of experiment. The in vitro drug release using the dialysis bag technique was characterized by a prolonged release. No burst effect was observed. Profilesare based on an anomalous transport and first order kinetics, regardless of the oil used. The in vitro microbiological test of nanocapsules suspensions was performed against Candida albicans and Candida glabrata susceptible and resistant to fluconazole by microdilution method. In combination with clotrimazole into nanoparticles, medium chain triglycerides was reported to have similar MICs of methanolic solution containing the oil and the drug. In addition to the antifungal activity in solution, coconut oil did not lose its activity after incorporation into the nanostructures and, in combination with drug, showed greater inhibition of microbial growth than the nanocapsules of medium chain triglycerides with clotrimazole. Finally nanoparticle suspensions were incorporated into hydrogels containing polymers with mucoadhesive properties, Pemulen® and Pullulan, which presented appropriate drug content, pH and spreadability. The formulations developed in this study represent promising alternatives for treatment of vulvovaginal candidiasis.